Characterization of Spirulina-Alginate Beads Formed Using Ionic Gelation - Rajmohan, Deepak (Int J Food Sci, 2019)
Spirulina (blue-green algae) is one of the cheapest sources of protein and essential vitamins. However, bitterness and bad flavor of spirulina protein may limit its use in food products. In this study, spirulina was encapsulated using ionic gelation to facilitate protein delivery. The objective was to study the effects of different types of gelation methods on particle size, texture, morphology, and crude protein content of the beads. Spirulina protein was encapsulated in alginate using both internal and external gelation methods and varying concentrations of sodium alginate and calcium chloride. A total of six different treatments were evaluated, and characterization of the beads included crude protein content, hardness measured using a texture analyzer, and thickness and width of the beads. The morphology was also studied using a scanning electron microscope (SEM). Results from the texture analysis show that the hardness of the external gelation beads is three times that of the internal gelation beads, and an increase in the alginate percentage in both gelation methods increased the firmness of the beads. The crude protein content was significantly higher with the beads formed using external gelation than with internal gelation. The SEM micrographs also show that the surface morphology of the beads produced with internal gelation has a more heterogeneous structure. Overall, the beads formed with external gelation were superior to those formed with internal gelation methods. Results from this study suggest that alginate is suitable for encapsulation of spirulina protein and these hydrogel beads could be used to enhance the protein delivery and facilitate the design of foods with alternative sources of protein.